2015
DOI: 10.3390/ijerph121012735
|View full text |Cite
|
Sign up to set email alerts
|

Noise Effects on Health in the Context of Air Pollution Exposure

Abstract: For public health policy and planning it is important to understand the relative contribution of environmental noise on health compared to other environmental stressors. Air pollution is the primary environmental stressor in relation to cardiovascular morbidity and mortality. This paper reports a narrative review of studies in which the associations of both environmental noise and air pollution with health have been examined. Studies of hypertension, myocardial infarction, stroke, mortality and cognitive outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(88 citation statements)
references
References 45 publications
(131 reference statements)
3
77
0
5
Order By: Relevance
“…Until recently, studies did not take into account exposures to traffic-related noise and air pollution simultaneously. A systematic review based on nine studies up to 2012 suggested a likely independent effect of both traffic-related noise and air pollution on cardiovascular disease (Tétreault et al, 2013), which was further supported by a recent updated review (Stansfeld, 2015) However, as only a handful of studies were 7 available, a definitive conclusion on the respective roles of air pollution and noise on cardiovascular disease cannot yet be drawn, and this issue warrants further research.…”
Section: Introductionmentioning
confidence: 90%
“…Until recently, studies did not take into account exposures to traffic-related noise and air pollution simultaneously. A systematic review based on nine studies up to 2012 suggested a likely independent effect of both traffic-related noise and air pollution on cardiovascular disease (Tétreault et al, 2013), which was further supported by a recent updated review (Stansfeld, 2015) However, as only a handful of studies were 7 available, a definitive conclusion on the respective roles of air pollution and noise on cardiovascular disease cannot yet be drawn, and this issue warrants further research.…”
Section: Introductionmentioning
confidence: 90%
“…Air pollution and noise in urban environments contribute disproportionately to cardiovascular and metabolic risk and disability, and account substantially to the burden of disease globally attributable to environmental factors. 1 In this review, we present the mechanistic evidence linking these factors with cardiovascular and metabolic disease, address unmet research needs and technology-aided solutions to further understand disease mechanisms and to mitigate their risk.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is weak evidence suggesting a link between noise and both depression and anxiety disorders [18]. Others report that residential noise exposure is associated with both self-assessed health and mental health status [19].…”
Section: Introductionmentioning
confidence: 99%